Teori Konflik: Sebuah Review atas Pemikiran Jonathan H. Turner - Hasnim Fadhly-Hassan (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2002)
As reflected in the title of his book, The Structure of Sociological Theory, Jonathan H. Turner explores the structure of sociological theories, categorizing them into five major perspectives: (1) functional theory, (2) conflict theory, (3) exchange theory, (4) interactionist theory, and (5) structuralist theory. Each of these perspectives has its own distinct sub-theories. This paper aims to review one of the perspectives discussed by Turner—conflict theory. Following Turner’s analytical structure, the review first examines the origins of conflict theory, which he traces back to Karl Marx, Georg Simmel, and Max Weber. The discussion then progresses to various perspectives within conflict theory, including Dahrendorf’s conflict theory, Coser’s functional conflict theory, and Collins’ exchange conflict theory. One of the most intriguing aspects of Turner’s approach is his effort to formulate theoretical propositions for each perspective. As he states in the introduction , a proposition is “a theoretical statement that specifies the connection between two or more variables.” These propositions, as formulated by Turner, have the potential to contribute significantly to theory building in sociological research.